Implementation And Challenges Of Discipline Character Education - Albet, Muhammad Sakin; Nasikhin, Nasikhin; Fihris, Fihris (Jurnal Pendidikan Karakter, 2024)
This article discusses the importance of discipline character education in forming a generation that is not only intellectually intelligent but also has strong moral values, especially in the era of globalization and technological advancement. The purpose of this study is to describe the implementation and challenges in discipline character education in Indonesia schools. The method used is a descriptive qualitative approach through literature review, which collects and analyzes data from various academic sources to understand the practice of discipline education. The results show that discipline serves as an educational tool to shape student behavior and includes various strategies, such as advice from teachers, role models, parental involvement, and the application of rules and habituation programs. However, challenges in the implementation of discipline character education arise from the lack of family support, the negative influence of friends, and unsupportive community environmental conditions. In conclusion, discipline character education is very important and requires cooperation between teachers, parents, and the community to create an environment that supports the development of students' character. This research is expected to contribute to the development of a more effective disciplinary character education model.